Antropogenic influence on the present genetic structure of forest tree populations - Nowakowska, Justyna Anna (Studia Ecologiae et Bioethicae, 2018)
Human activity has always had an impact on the species composition and genetic structure of species that make up the forest ecosystem. The results of DNA-based studies confirm the influence of current and past forest management on the current level of genetic variability of forest tree populations. Molecular analysis enables the study of gene flow between generations and reflects the history of post-glacial migration of species from southern refugia of Europe to Poland. Thanks to DNA markers, it is possible to precisely distinguish species hybrids, e.g. between Japanese and European larches. In timber trade market, the comparison of the DNA profiles of a stolen tree with a stump left in the forest provides strong evidence in judiciary pursuits concerning the illegal logging. Genetic transformation of the tree genome allows to obtain wood with altered lignin structure, higher increment and increased assimilation of CO2 in the leaves. Genetic modifications are also aimed at enhanced immunity of cultured tree species to fungal pathogens or insect pests and to plant protection products on fast-growing GMO trees.